2021
DOI: 10.1101/2021.08.24.21262563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A community based case-control study to determine the risk factors of dengue fever in Bangladesh

Abstract: In a tropical country like Bangladesh where the climatic condition favors the growth of Aedes mosquito vectors, the success of dengue prevention depends largely on the proper identification and controlling of the socio-demographic and lifestyle-related risk factors. A case-control study including 150 cases and 150 controls were conducted aimed to explore the potential risk and protective factors and their association with dengue virus infection in the Chattogram district of Bangladesh. Cases were confirmed for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The transmission of the viruses occurs between 18 and 34 °C and peaks in the range of 26-29 °C (Mordecai et al 2017). However, previous studies in different countries showed a range of combinations of various surrounding environmental parameters on dengue transmission (Choi et al 2016;Johansson et al 2016;Rahman et al 2021a). The literature also stated that temperature, rainfall, relative humidity, and population density were associated with dengue infection in high-risk areas (Zhu et al 2016;Sharmin et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of the viruses occurs between 18 and 34 °C and peaks in the range of 26-29 °C (Mordecai et al 2017). However, previous studies in different countries showed a range of combinations of various surrounding environmental parameters on dengue transmission (Choi et al 2016;Johansson et al 2016;Rahman et al 2021a). The literature also stated that temperature, rainfall, relative humidity, and population density were associated with dengue infection in high-risk areas (Zhu et al 2016;Sharmin et al 2018).…”
Section: Introductionmentioning
confidence: 99%